(3MOjK GdRgQis - (3CHh eMeO GdMSf Hf Ydj Hf eMeO Hf GdMSf GdLhgQi GdebfYis; (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s
(3ChdgG (B:s
(3CNHQfG GdTjN GdKbI CHh eMeO GdLhgQi GdebfYi eeG bQCg Ydjg GdXGgQ GdfjSGHhQi bGd bGd QShd Gddg Udi Gddg Ydjg hSde (B( (3Chd ReQI ef CeJi JONd GdLfI Ydi eKd UhQI GdbeQ djdI GdHOQ s
(3BNQgG (B:s
(3jbhd SeYJ TgO GdMQK QVi Gddg Yfg jbhd Gddg e GSJQ hGLYd JMJ GdSJQ eG JMH aQHeG SJQJ Ydi eG JcQg hGdMeO ddg hMOg hUdhGJg Ydi NjQ Ndbg eMeO GdfHi hBdg hSde JSdjekG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B79s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs